Severe Thrombocytopenic Purpura in a Child with Brucellosis: Case Presentation and Review of the Literature - Alexandros Makis; Aikaterini Perogiannaki; Nikolaos Chaliasos (Case Reports in Infectious Diseases)
Brucellosis is still endemic and a significant public health problem in many Mediterranean countries, including Greece. It is a multisystemic disease with a broad spectrum of clinical manifestations including hematological disorders, such as anemia, pancytopenia, leucopenia, and thrombocytopenia. Thrombocytopenia is usually moderate and attributed to bone marrow suppression or hypersplenism. Rarely, autoimmune stimulation can cause severe thrombocytopenia with clinically significant hemorrhagic manifestations. We present the case of a girl with severe thrombocytopenic purpura as one of the presenting symptoms of Brucella melitensis infection. Treatment with intravenous immunoglobulin and the appropriate antimicrobial agents promptly resolved the thrombocyte counts. A review of similar published cases is also presented.